El Colibri Mediano (Colibri serrirostris) en el noreste de Argentina - Pagano, Luis G.; Bodrati, Alejandro; Fariña, Néstor; Villalba, Olga (Nuestras Aves, 2018)
Este artículo no cuenta con un resumen.